A high-hardness wear-resistant composite coating, a tool and a preparation method thereof
Patent Information
- Application Number
- CN202611239022.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-16
- Publication Date
- 2026-10-09
AI Technical Summary
[0031]本申请提供了一种高硬度耐磨复合涂层,应用于具有刃部的刀具,高硬度耐磨复合涂层通过电弧离子镀形成于刀具的刃部表面。高硬度耐磨复合涂层包括高熵合金层和高熵氮化物层,高熵合金层与高熵氮化物层形成梯度过渡结构或周期性交替的多层复合结构。高熵合金层的元素包括铝、钛、铬、钼、硅和铌,高熵合金层的相结构为面心立方晶格与体心立方晶格的混合结构。
Smart Images

Figure CN122879654A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite coating technology, and in particular to a high-hardness wear-resistant composite coating, a cutting tool, and a method for preparing the same. Background Technology
[0002] Kitchen knives, as tools for processing food in home cooking and the catering industry, have diverse uses, including slicing, chopping, and bone cutting. Currently, high-quality kitchen knives need to balance high hardness, wear resistance, and food contact safety.
[0003] Traditional kitchen knives are mostly manufactured from a single piece of stainless steel or carbon steel. However, the quality of kitchen knives is limited by the physical properties of a single material. To overcome the limitations of a single material, the industry has used laser cladding technology to create a coating on the substrate surface, thereby improving overall performance through surface strengthening. However, the precision of the laser cladding process is difficult to control, easily resulting in defects such as uneven coating thickness, localized porosity, and inclusions. This presents a challenge in balancing production costs and yield rates, hindering the large-scale promotion and widespread adoption of this technology in kitchen knives.
[0004] Therefore, there is a need to develop a new coating technology to form a high-hardness, wear-resistant functional coating on kitchen knives. Summary of the Invention
[0005] To address the technical problems existing in the prior art, the present invention aims to provide a high-hardness wear-resistant composite coating, a cutting tool, and a method for preparing the same.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] In a first aspect, this application provides a high-hardness wear-resistant composite coating applied to a cutting tool with a cutting edge. The high-hardness wear-resistant composite coating is formed on the cutting edge surface of the cutting tool by arc ion plating.
[0008] The high-hardness wear-resistant composite coating includes a high-entropy alloy layer and a high-entropy nitride layer. The high-entropy alloy layer and the high-entropy nitride layer form a gradient transition structure or a periodically alternating multi-layer composite structure.
[0009] The elements in the high-entropy alloy layer include aluminum, titanium, chromium, molybdenum, silicon, and niobium. The phase structure of the high-entropy alloy layer is a mixed structure of face-centered cubic lattice and body-centered cubic lattice.
[0010] In one embodiment, the high-entropy alloy layer comprises the following elements by atomic percentage: 12%–18% aluminum, 18%–25% titanium, 18%–25% chromium, 8%–12% molybdenum, 5%–10% silicon, and 18%–25% niobium.
[0011] In one embodiment, the elements of the high-entropy nitride layer include nitrogen, aluminum, titanium, chromium, molybdenum, silicon, and niobium, and the phase structure of the high-entropy nitride layer is a single-phase face-centered cubic solid solution structure.
[0012] In one embodiment, the high-entropy alloy layer and the high-entropy nitride layer form a periodically alternating multilayer composite structure;
[0013] The high-entropy nitride layer contains the following elements by atomic percentage: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, and niobium 7%–12%.
[0014] In one embodiment, the thickness ratio of the high-entropy nitride layer to the high-entropy alloy layer is 3 to 4:1;
[0015] The multilayer composite structure formed by the high-entropy nitride layer and the high-entropy alloy layer includes 12 to 20 modulation cycles, and the thickness of each modulation cycle is 200 nm to 300 nm.
[0016] In one embodiment, the high-entropy alloy layer and the high-entropy nitride layer form a gradient transition structure. The high-entropy nitride layer contains the following elements by atomic percentage: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, niobium 7%–12%, erbium 0.1%–2.0%, and boron 0.5%–5.0%.
[0017] In one embodiment, the high-hardness wear-resistant composite coating further includes a bonding layer disposed between the blade surface and the high-entropy alloy layer. The bonding layer is formed by an arc ion plating process on a titanium target, and the thickness of the bonding layer is 300 nm to 500 nm.
[0018] Secondly, this application provides a knife, which is a kitchen knife, and the blade surface of the knife is provided with a high-hardness wear-resistant composite coating as described in the first aspect.
[0019] In one embodiment, the high-hardness wear-resistant composite coating includes a bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer; the bonding layer is formed by an arc ion plating process using a titanium target.
[0020] The high-entropy alloy layer contains the following elements by atomic percentage: aluminum 12%–18%, titanium 18%–25%, chromium 18%–25%, molybdenum 8%–12%, silicon 5%–10%, and niobium 18%–25%;
[0021] The high-entropy nitride layer contains the following elements by atomic percentage: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, and niobium 7%–12%;
[0022] The thickness ratio of the high-entropy nitride layer to the high-entropy alloy layer is 4:1. The high-entropy alloy layer and the high-entropy nitride layer form a periodically alternating multilayer composite structure, which includes 16 modulation cycles, and the thickness of each modulation cycle is 200nm to 300nm.
[0023] Thirdly, this application provides a method for preparing a cutting tool according to the second aspect, the method comprising:
[0024] The sharpened kitchen knife body is cleaned and dried in an ultrasonic cleaning line, and then mounted on the workpiece rack in the vacuum coating chamber; the vacuum coating chamber is evacuated to a back vacuum level of 1.5 × 10⁻⁶. -3 Pa ~ 3.0 × 10 -3 Pa, and the temperature is increased to 400℃~480℃;
[0025] Argon gas is introduced into the vacuum coating chamber, and the gas pressure is controlled at 0.3Pa to 0.6Pa. The bias voltage of the kitchen knife substrate is controlled at -200V to -300V. The surface of the kitchen knife substrate is subjected to argon ion bombardment etching and cleaning for 25min to 50min.
[0026] Using a titanium target as the target source, an arc ion plating process is used to deposit a bonding layer on the surface of the kitchen knife substrate;
[0027] Using an AlTiCrMoSiNb high-entropy alloy target as the arc target; under an argon atmosphere without nitrogen, turn on the arc target power supply, control the target current to be 120A~160A, and the substrate bias voltage to be -60V~-120V, and deposit a high-entropy alloy layer on the bonding layer.
[0028] Under a nitrogen atmosphere, the gas pressure is controlled at 1.5 Pa to 3 Pa, the arc target power supply is turned on, the target current is controlled at 120 A to 160 A, the substrate bias voltage is -60 V to -120 V, and a high-entropy nitride layer is deposited.
[0029] By alternating the introduced gas atmosphere and controlling the deposition time, the high-entropy alloy layer and the high-entropy nitride layer are periodically deposited alternately at a single-layer thickness ratio of 1:4, forming a multilayer composite structure containing 16 modulation cycles with a thickness of 200nm to 300nm for each modulation cycle.
[0030] Compared with existing technologies, the high-hardness wear-resistant composite coating, cutting tool, and preparation method of the present invention have at least the following beneficial effects:
[0031] This application provides a high-hardness, wear-resistant composite coating for use on cutting tools with a cutting edge. The high-hardness, wear-resistant composite coating is formed on the cutting edge surface of the tool by arc ion plating. The high-hardness, wear-resistant composite coating includes a high-entropy alloy layer and a high-entropy nitride layer, with the high-entropy alloy layer and the high-entropy nitride layer forming a gradient transition structure or a periodically alternating multilayer composite structure. The elements in the high-entropy alloy layer include aluminum, titanium, chromium, molybdenum, silicon, and niobium, and the phase structure of the high-entropy alloy layer is a mixed structure of face-centered cubic and body-centered cubic lattices.
[0032] This application employs an arc ion plating process to prepare a composite coating on the cutting edge of a knife, consisting of a high-entropy alloy layer and a high-entropy nitride layer. The coating can adopt a gradient transition structure or a periodically alternating multi-layer composite structure. The coating formed by the arc ion plating process is uniform and dense, less prone to defects such as porosity and inclusions, which is beneficial for improving yield and adapting to large-scale production. At the same time, the gradient or multi-layer composite structure can alleviate coating stress and inhibit crack propagation. The high-entropy alloy layer and the high-entropy nitride layer give the knife cutting edge both high hardness and good toughness, effectively improving the wear resistance and edge protection of the kitchen knife. Furthermore, the coating structure is stable, meeting the safety requirements for food contact use, and overcoming the performance limitations of traditional single-material kitchen knives. Attached Figure Description
[0033] Figure 1 This is a photograph of the actual coating sample.
[0034] Figure 2 SEM morphology of cross-sections of composite coatings with different modulation periods. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0037] This application provides a high-hardness, wear-resistant composite coating applied to a cutting tool with a cutting edge. The high-hardness, wear-resistant composite coating is deposited on the cutting edge surface of the tool via arc ion plating (AIP) to improve the surface hardness, wear resistance, and cutting life of the cutting edge.
[0038] In some embodiments, the high-hardness wear-resistant composite coating includes a bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer. The bonding layer is deposited on the cutting edge substrate surface of the tool, and the high-entropy alloy layer and the high-entropy nitride layer form a gradient transition structure or a periodically alternating multilayer composite structure on the bonding layer.
[0039] The bonding layer is positioned between the tool substrate and the high-entropy alloy layer to enhance the interfacial bonding strength between the coating and the tool substrate, reducing the risk of peeling off the coating during long-term use. The high-entropy alloy layer is positioned above the bonding layer, and the high-entropy nitride layer is positioned on the surface of the high-entropy alloy layer. Through the synergistic effect between the high-entropy alloy layer and the high-entropy nitride layer, the composite coating possesses high hardness, wear resistance, and impact resistance.
[0040] In some embodiments, the high-entropy alloy layer and the high-entropy nitride layer form a gradient transition structure. In this structure, the metal element content in the high-entropy alloy layer gradually varies along the coating thickness direction, and through the gradual introduction of nitrogen, the high-entropy alloy layer gradually transforms into a high-entropy nitride layer, thereby forming a gradient transition structure with continuously changing composition. This gradient structure can reduce the interfacial stress caused by differences in lattice structure and thermal expansion coefficients between different material layers, improve the overall bonding strength of the coating, and enhance the stability of the coating.
[0041] In other embodiments, the high-entropy alloy layer and the high-entropy nitride layer form a periodically alternating multilayer composite structure. Specifically, the high-entropy alloy layer and the high-entropy nitride layer are alternately deposited along a direction perpendicular to the tool cutting edge surface to form multiple composite periodic units, each composite periodic unit including at least one high-entropy alloy layer and at least one high-entropy nitride layer. By periodically alternating these layers, multiple interface barriers are created between different functional layers, increasing the complexity of the crack propagation path and thereby improving the crack propagation resistance and wear resistance of the composite coating.
[0042] In one specific implementation, the high-entropy alloy layer is composed of six elements: aluminum (Al), titanium (Ti), chromium (Cr), molybdenum (Mo), silicon (Si), and niobium (Nb), forming an alloy structure with a high-entropy effect through a multi-principal element alloying method.
[0043] The high-entropy alloy layer contains the following elements by atomic percentage: 12%–18% aluminum, 18%–25% titanium, 18%–25% chromium, 8%–12% molybdenum, 5%–10% silicon, and 18%–25% niobium. In some embodiments, the content of each element in the high-entropy alloy layer can be adjusted according to the operating conditions of the cutting tool and the requirements for the coating's hardness, toughness, and wear resistance.
[0044] In the aforementioned high-entropy alloy layers, aluminum promotes the stability of the alloy's crystal structure and enhances the coating's hardness and oxidation resistance through solid solution strengthening. Titanium improves the bonding stability between the alloy layer and subsequent nitride layers, while also facilitating the formation of high-hardness nitride phases. Chromium improves the coating's wear resistance and high-temperature stability. Molybdenum enhances the alloy layer's resistance to plastic deformation and improves the coating's structural stability under high-temperature friction conditions. Silicon promotes the formation of amorphous phase structures, increases coating density, and reduces crack propagation tendency. Niobium, with its high melting point and excellent solid solution strengthening effect, improves the coating's strength and heat resistance.
[0045] In some embodiments, the aluminum content in the high-entropy alloy layer can be 12%, 13%, 14%, 15%, 16%, 17%, or 18%; the titanium content can be 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%; the chromium content can be 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%; the molybdenum content can be 8%, 9%, 10%, 11%, or 12%; the silicon content can be 5%, 6%, 7%, 8%, 9%, or 10%; and the niobium content can be 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%.
[0046] Furthermore, the phase structure of the high-entropy alloy layer is a hybrid structure of face-centered cubic (FCC) and body-centered cubic (BCC) lattices. The FCC structure provides better plastic deformation capacity and toughness, giving the high-entropy alloy layer better fracture resistance when the tool is subjected to impact loads or cyclic cutting loads; the BCC structure provides higher strength and hardness, which is beneficial for improving the coating's resistance to abrasive wear and cutting friction. Furthermore, the phase structure of the high-entropy alloy layer is a hybrid structure of face-centered cubic and body-centered cubic lattices.
[0047] In some embodiments, by adjusting the ratio of aluminum, titanium, chromium, molybdenum, silicon, and niobium in the high-entropy alloy layer, the ratio of face-centered cubic (FCC) to body-centered cubic (BCC) lattice structures can be controlled, enabling the high-entropy alloy layer to possess both high hardness and good toughness. For example, increasing the content of chromium, molybdenum, or niobium helps to increase the proportion of BCC structure, thereby enhancing the coating hardness; appropriately increasing the content of aluminum and titanium helps to stabilize the FCC lattice structure and improve the ductility and toughness of the coating.
[0048] In one specific embodiment, the high-entropy alloy layer is formed by arc ion plating. Specifically, a high-entropy alloy target containing aluminum, titanium, chromium, molybdenum, silicon, and niobium is used as the deposition source. Under vacuum and inert gas protection conditions, the target elements are ionized by arc discharge to form high-energy metal ions, which are then deposited on the surface of the bonding layer to form the high-entropy alloy layer.
[0049] During the deposition process, by controlling the target composition, deposition temperature, working gas pressure, substrate bias, and deposition time, the high-entropy alloy layer forms an FCC / BCC dual-phase crystal structure, thereby improving the interfacial bonding performance between the high-entropy alloy layer and the high-entropy nitride layer, and providing a structural basis for the subsequent formation of a high-hardness, wear-resistant composite coating. Through the synergistic effect of the high-entropy alloy layer and the high-entropy nitride layer, the resulting composite coating exhibits both high hardness and high wear resistance.
[0050] In one optional embodiment, the initial atomic percentage content of each metal element in the high-entropy alloy target used to form the high-entropy alloy layer and the high-entropy nitride layer is as follows: aluminum 13%–18%, titanium 18%–22%, chromium 18%–22%, molybdenum 8%–12%, silicon 6%–10%, and niobium 20%–26%. By controlling the evaporation and ionization of the target material with the above-mentioned proportions during the arc ion plating process, the atomic percentage distribution of each metal element in the deposited high-entropy alloy layer and high-entropy nitride layer can be controlled within the range described herein.
[0051] Specifically, based on the aforementioned high-entropy alloy layer, this application provides two implementations of high-entropy nitride layers, including:
[0052] Implementation method (1): A multilayer composite structure with periodic alternation of high-entropy alloy layer and high-entropy nitride layer is formed.
[0053] Specifically, the high-entropy nitride layer includes nitrogen, aluminum, titanium, chromium, molybdenum, silicon, and niobium. The aluminum, titanium, chromium, molybdenum, silicon, and niobium elements correspond to the metal elements in the high-entropy alloy layer, enabling the high-entropy nitride layer to form a nitride-reinforced structure by introducing nitrogen elements on the basis of the high-entropy alloy layer.
[0054] Furthermore, based on atomic percentage content, the high-entropy nitride layer contains the following elements: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, and niobium 7%–12%.
[0055] In some embodiments, the nitrogen content in the high-entropy nitride layer can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%; the aluminum content can be 6%, 7%, 8%, 9%, or 10%; the titanium content can be 9%, 10%, 11%, 12%, 13%, or 14%; the chromium content can be 9%, 10%, 11%, 12%, 13%, or 14%; the molybdenum content can be 3%, 4%, 5%, 6%, or 7%; the silicon content can be 2%, 3%, 4%, 5%, or 6%; and the niobium content can be 7%, 8%, 9%, 10%, 11%, or 12%.
[0056] Furthermore, in this embodiment (I), the phase structure of the high-entropy nitride layer is a single-phase face-centered cubic solid solution structure. Because the high-entropy nitride layer forms a face-centered cubic lattice structure through a multi-principal element synergistic solid solution process, different metal elements generate lattice distortion effects within the lattice, thereby improving the ability to impede dislocation movement and enhancing the coating's hardness and resistance to plastic deformation. Simultaneously, the single-phase face-centered cubic solid solution structure avoids localized stress concentration caused by multiphase interface defects, improving the coating's structural stability.
[0057] In this embodiment, the high-entropy nitride layer and the high-entropy alloy layer are alternately deposited along a direction perpendicular to the surface of the cutting edge to form multiple modulation cycles. Specifically, each modulation cycle includes a high-entropy alloy layer and a high-entropy nitride layer disposed on the surface of the high-entropy alloy layer. By repeating multiple modulation cycles, the composite coating forms a multilayer structure with periodic interfaces.
[0058] Furthermore, the thickness ratio of the high-entropy nitride layer to the high-entropy alloy layer is 3–4:1. That is, within each modulation cycle, the thickness of the high-entropy nitride layer is 3–4 times the thickness of the high-entropy alloy layer. By increasing the thickness ratio of the high-entropy nitride layer, the composite coating surface has a higher proportion of nitride-reinforced regions, thereby improving the wear resistance and friction resistance of the tool cutting edge during contact with the workpiece material. At the same time, by retaining a certain thickness of the high-entropy alloy layer, the multilayer structure maintains good toughness buffering capacity, reducing the risk of brittle cracking of the hard nitride layer under impact loads.
[0059] In some embodiments, the multilayer composite structure formed by the high-entropy nitride layer and the high-entropy alloy layer includes 12 to 20 modulation cycles. Specifically, the number of modulation cycles can be 12, 13, 14, 15, 16, 17, 18, 19, or 20. By setting multiple modulation cycles, multiple heterogeneous interfaces are formed inside the composite coating. When cracks propagate inside the coating, they need to pass through multiple interfaces between the high-entropy alloy layer and the high-entropy nitride layer, thereby increasing the crack propagation path and improving the crack propagation resistance of the composite coating.
[0060] Furthermore, the thickness of each modulation cycle is 200 nm to 300 nm. Specifically, the thickness of each modulation cycle can be 200 nm, 220 nm, 240 nm, 250 nm, 260 nm, 280 nm, or 300 nm. By controlling the modulation cycle thickness, both the high-entropy nitride layer and the high-entropy alloy layer are kept within the nanoscale range, thereby fully leveraging the interface strengthening effect of the multilayer structure.
[0061] In some embodiments, high-entropy nitride layers and high-entropy alloy layers are formed by alternating deposition of high-entropy alloy layers via an arc ion plating process. During deposition, a high-entropy alloy target containing aluminum, titanium, chromium, molybdenum, silicon, and niobium is first deposited on the surface of the cutting tool to form a high-entropy alloy layer. Subsequently, nitrogen gas is introduced to react the metal elements with nitrogen, depositing a high-entropy nitride layer on the surface of the high-entropy alloy layer. By repeating the above deposition process, a multilayer composite structure with periodic alternation of high-entropy alloy layers and high-entropy nitride layers with multiple modulation cycles is obtained.
[0062] In the above embodiments, by periodically alternating high-entropy alloy layers with an FCC / BCC hybrid structure and high-entropy nitride layers with a single-phase face-centered cubic solid solution structure, a multi-scale, multi-interface reinforcement structure is formed within the composite coating. The high-entropy nitride layer provides higher hardness and wear resistance, while the high-entropy alloy layer provides toughness support and stress relief. The multi-layered interfaces further hinder crack propagation, thereby improving the overall performance of the high-hardness, wear-resistant composite coating formed on the cutting edge surface of the tool.
[0063] Implementation method (2): The high-entropy alloy layer and the high-entropy nitride layer form a gradient transition structure.
[0064] By continuously adjusting the elemental composition along the coating thickness direction, the high-entropy alloy layer gradually transitions to a high-entropy nitride layer, thereby reducing the interfacial stress between the two materials and improving the overall bonding performance of the composite coating. The high-entropy nitride layer, by atomic percentage, contains the following elements: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, niobium 7%–12%, erbium 0.1%–2.0%, and boron 0.5%–5.0%.
[0065] In some embodiments, the nitrogen content in the high-entropy nitride layer can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%; the aluminum content can be 6%, 7%, 8%, 9%, or 10%; the titanium content can be 9%, 10%, 11%, 12%, 13%, or 14%; the chromium content can be 9%, 10%, 11%, 12%, 13%, or 14%; the molybdenum content can be 3%, 4%, 5%, 6%, or 7%; the silicon content can be 2%, 3%, 4%, 5%, or 6%; the niobium content can be 7%, 8%, 9%, 10%, 11%, or 12%; the erbium content can be 0.1%, 0.5%, 1.0%, 1.5%, or 2.0%; and the boron content can be 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, or 5.0%.
[0066] Furthermore, in the gradient transition structure, there is no obvious material interface between the high-entropy alloy layer and the high-entropy nitride layer; instead, a continuously varying compositional gradient region is formed along the coating thickness direction. Specifically, in the region closer to the high-entropy alloy layer, the content of metallic elements is higher and the content of nitrogen elements is lower, enabling this region to maintain good toughness and plastic deformation capacity. As one moves away from the high-entropy alloy layer and closer to the coating surface, the nitrogen content gradually increases, gradually forming a hard region dominated by the high-entropy nitride phase, giving the coating surface high hardness and wear resistance.
[0067] It is understood that the gradient transition structure includes a gradient transition region in which the high-entropy alloy phase gradually transforms into the high-entropy nitride phase; within the gradient transition region, as the direction extends away from the tool substrate surface, nitrogen gradually participates in the lattice formation process, causing the nitrogen content to gradually increase, thereby achieving a continuous transition from the high-entropy alloy layer to the high-entropy nitride layer.
[0068] In this embodiment, erbium, as a rare earth element, is introduced into the high-entropy nitride layer. This regulates the grain growth behavior of the coating, refines the grain size, and improves the uniformity of the coating structure. Simultaneously, erbium enhances the structural stability of the coating. Boron promotes the formation of amorphous structures in the high-entropy nitride layer and forms stable boride reinforcing phases with metallic elements, resulting in grain refinement and interface strengthening within the coating. Through the synergistic effect of boron and silicon, the density of the high-entropy nitride layer can be further improved, reducing internal defects and enhancing the coating's wear resistance and crack propagation resistance.
[0069] Furthermore, the crystal structure of the high-entropy nitride layer can be a composite structure composed of a face-centered cubic solid solution structure and an amorphous reinforcing phase. In some embodiments, by controlling the addition ratio of erbium and boron, the high-entropy nitride layer maintains a nanocrystalline structure and forms silicon-rich and boron-rich amorphous phases in the grain boundary regions, thereby improving the overall performance of the coating in terms of hardness and toughness.
[0070] In some specific embodiments, the gradient transition structure is achieved by continuously adjusting the reaction atmosphere during the arc ion plating process. Specifically, in the initial stage of deposition, a high-entropy alloy target containing aluminum, titanium, chromium, molybdenum, silicon, and niobium is deposited to form a high-entropy alloy layer with good adhesion to the tool substrate. Subsequently, the nitrogen gas injection rate is gradually increased, causing the nitrogen content to gradually increase along the thickness direction during deposition. At the same time, erbium- and boron-containing control sources are introduced to gradually transition the coating from a high-entropy alloy layer to a high-entropy nitride layer, ultimately obtaining a gradient transition structure.
[0071] Based on the above embodiments, the high-hardness wear-resistant composite coating also includes a bonding layer disposed between the blade surface and the high-entropy alloy layer. The bonding layer is formed by an arc ion plating process on a titanium target, and the thickness of the bonding layer is 300 nm to 500 nm.
[0072] Based on the above embodiments, the high-hardness wear-resistant composite coating also includes a bonding layer disposed between the tool cutting edge surface and the high-entropy alloy layer. The bonding layer is used to improve the interfacial bonding strength between the high-hardness wear-resistant composite coating and the tool substrate, and reduce the risk of peeling or detachment of the composite coating under long-term cutting, friction, and impact loads.
[0073] Specifically, the bonding layer uses a titanium target as the deposition source and is formed on the surface of the cutting edge of the tool through an arc ion plating (AIP) process. During the deposition process, the titanium target generates high-energy titanium ions through arc discharge in a vacuum environment. Under the action of substrate bias voltage, the high-energy titanium ions are accelerated to bombard the surface of the cutting edge of the tool and deposit to form a continuous and dense titanium metal bonding layer.
[0074] In some embodiments, before forming the bonding layer, the surface of the cutting edge can be pretreated to remove oil, oxides, and adsorbed impurities, thereby increasing the activity of the tool substrate surface. Subsequently, the cutting edge surface is cleaned by argon ion bombardment, which creates a certain degree of micro-roughness on the tool substrate surface, thereby increasing the mechanical interlocking between the bonding layer and the tool substrate.
[0075] Furthermore, the thickness of the bonding layer is 300 nm to 500 nm. Specifically, the thickness of the bonding layer can be 300 nm, 350 nm, 400 nm, 450 nm, or 500 nm. Within this thickness range, the bonding layer can form a stable transition region between the tool substrate and the high-entropy alloy layer, ensuring sufficient interfacial bonding strength while avoiding a decrease in the overall hardness of the composite coating due to excessive bonding layer thickness.
[0076] In some embodiments, the titanium element in the bonding layer can achieve a good elemental transition with the titanium element in the subsequently deposited high-entropy alloy layer, which helps to reduce the abrupt change in composition between the bonding layer and the high-entropy alloy layer and improves the interlayer bonding stability. Meanwhile, titanium metal has good ductility and toughness. By setting a titanium bonding layer, a stable transition interface is formed between the tool cutting edge substrate and the high-entropy alloy layer, improving the overall adhesion of the composite coating; at the same time, the continuous elemental transition between the bonding layer and the high-entropy alloy layer reduces the interfacial stress caused by lattice differences and thermal expansion differences between different materials.
[0077] In this application embodiment, a knife is provided, which is a kitchen knife, and the blade surface of the knife is provided with the above-mentioned high hardness wear-resistant composite coating.
[0078] Specifically, the aforementioned high-hardness wear-resistant composite coating is applied to the blade surface of the kitchen knife. This high-hardness wear-resistant composite coating is formed on the blade surface using an arc ion plating process and sequentially comprises a bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer. The bonding layer is positioned between the kitchen knife substrate and the high-entropy alloy layer to enhance the bonding strength between the coating and the substrate; the high-entropy alloy layer provides good toughness support and stress buffering; and the high-entropy nitride layer is positioned on the outer side to improve the hardness, wear resistance, and anti-cutting wear ability of the blade surface.
[0079] In some embodiments, the knife body can be made of stainless steel, such as martensitic stainless steel, chromium-molybdenum steel, or other high-strength steels suitable for knife manufacturing. After heat treatment, fine grinding, and sharpening, the knife body achieves an initial sharpness that meets cutting requirements. Then, the high-hardness, wear-resistant composite coating is deposited on the surface of the knife body using an arc ion plating process.
[0080] In one specific implementation, the high-hardness wear-resistant composite coating on the kitchen knife substrate includes a bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer; the bonding layer is formed by an arc ion plating process on a titanium target.
[0081] The high-entropy alloy layer contains the following elements by atomic percentage: aluminum 12%–18%, titanium 18%–25%, chromium 18%–25%, molybdenum 8%–12%, silicon 5%–10%, and niobium 18%–25%;
[0082] The high-entropy nitride layer contains the following elements by atomic percentage: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, and niobium 7%–12%;
[0083] The thickness ratio of the high-entropy nitride layer to the high-entropy alloy layer is 4:1. The high-entropy alloy layer and the high-entropy nitride layer form a periodically alternating multilayer composite structure, which includes 16 modulation cycles, and the thickness of each modulation cycle is 200nm to 300nm.
[0084] Through the above structural design, the surface of the kitchen knife blade in this embodiment forms a high-hardness, wear-resistant composite coating composed of a bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer. The bonding layer improves the bonding stability between the coating and the blade substrate; the high-entropy alloy layer provides toughness support and stress buffering; the high-entropy nitride layer provides high hardness and wear-resistant protection; and the multi-layered, periodically alternating structure further enhances the coating's resistance to crack propagation, enabling the kitchen knife to maintain good sharpness and durability during long-term cutting use.
[0085] In one specific embodiment, this application also provides a method for preparing a knife, which is used to prepare a kitchen knife with a high-hardness, wear-resistant composite coating. A bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer are sequentially formed on the surface of the kitchen knife substrate using an arc ion plating process, and a multi-layer composite structure is formed through periodic alternating deposition.
[0086] In one specific embodiment, this application also provides a method for preparing a cutting tool, the method comprising:
[0087] First, the knife substrate after sharpening undergoes pretreatment. The sharpened knife substrate is placed in an ultrasonic cleaning line to remove oil, grinding residue, and other contaminants from the blade surface. After cleaning, the knife substrate is dried to remove residual moisture. Then, the treated knife substrate is mounted on a workpiece holder in the vacuum coating chamber, ensuring the blade area is within the coating deposition area.
[0088] Furthermore, the vacuum coating chamber is evacuated to achieve a back vacuum level of 1.5 × 10⁻⁶. -3 Pa ~ 3.0 × 10 -3 Pa, and the vacuum coating chamber is heated to maintain the temperature at 400℃~480℃ during the coating process.
[0089] Subsequently, the surface of the kitchen knife substrate was subjected to ion bombardment etching and cleaning. Specifically, argon gas was introduced into the vacuum coating chamber, and the working gas pressure was controlled at 0.3 Pa to 0.6 Pa. At the same time, the bias voltage of the kitchen knife substrate was controlled at -200 V to -300 V, and the surface of the kitchen knife substrate was bombarded with argon ions for 25 min to 50 min.
[0090] After ion bombardment etching and cleaning, a bonding layer is deposited on the surface of the kitchen knife substrate. Specifically, using a titanium target as the target source, titanium is deposited on the blade surface of the kitchen knife substrate through an arc ion plating process, forming a continuous and dense titanium bonding layer. This bonding layer serves as a transition area between the kitchen knife substrate and the subsequent high-entropy alloy layer, improving the overall adhesion strength of the composite coating.
[0091] Furthermore, after the bonding layer is formed, a high-entropy alloy layer is deposited. Specifically, an AlTiCrMoSiNb high-entropy alloy target is used as an arc target. The arc target power supply is turned on under an argon atmosphere without nitrogen, so that the metal elements such as aluminum, titanium, chromium, molybdenum and niobium in the high-entropy alloy target are ionized and deposited onto the surface of the bonding layer.
[0092] During the deposition of the high-entropy alloy layer, the target current was controlled at 120A to 160A, and the bias voltage of the kitchen knife substrate was controlled at -60V to -120V. By controlling the above deposition parameters, the high-entropy alloy layer forms a transitional reinforcement layer with a stable microstructure, providing a good structural basis for the subsequent deposition of the high-entropy nitride layer.
[0093] Subsequently, a high-entropy nitride layer is deposited on the surface of the high-entropy alloy layer. Specifically, nitrogen gas is introduced into the vacuum coating chamber to change the deposition environment from an inert gas environment to a reactive atmosphere environment, and the working gas pressure is controlled at 1.5 Pa to 3 Pa; the arc target power supply is turned on, so that elements such as aluminum, titanium, chromium, molybdenum, silicon and niobium in the high-entropy alloy target react with nitrogen elements to form a high-entropy nitride layer on the surface of the high-entropy alloy layer.
[0094] During the deposition of the high-entropy nitride layer, the target current is controlled at 120A to 160A, and the bias voltage of the kitchen knife substrate is controlled at -60V to -120V, so that the high-entropy nitride layer has high density and good mechanical properties.
[0095] Furthermore, by alternating the gas atmosphere in the vacuum coating chamber and controlling the deposition time of the high-entropy alloy layer and the high-entropy nitride layer, the high-entropy alloy layer and the high-entropy nitride layer are periodically deposited alternately at a single-layer thickness ratio of 1:4.
[0096] Specifically, an argon protective atmosphere is maintained during the deposition of the high-entropy alloy layer, allowing the metal elements in the high-entropy alloy target to be directly deposited to form the high-entropy alloy layer; nitrogen gas is introduced during the deposition of the high-entropy nitride layer to create a reactive atmosphere, causing the metal elements to react with nitrogen elements to form the high-entropy nitride layer. By repeating the above deposition process, a multi-layered composite structure with periodically alternating high-entropy alloy layers and high-entropy nitride layers is formed.
[0097] In this embodiment, the multilayer composite structure includes 16 modulation cycles, each with a thickness of 200 nm to 300 nm. By setting multiple modulation cycles, multiple nanoscale heterogeneous interfaces are formed between the high-entropy alloy layer and the high-entropy nitride layer. When the tool is subjected to frictional or impact loads during cutting, the crack propagation path is hindered by multiple heterogeneous interfaces, thereby improving the crack propagation resistance of the composite coating.
[0098] Furthermore, in the high-hardness wear-resistant composite coating formed by the above preparation method, the bonding layer can improve the bonding strength between the coating and the kitchen knife substrate, the high-entropy alloy layer can provide toughness support and stress buffering, the high-entropy nitride layer can provide high hardness and wear-resistant protection, and the multi-layer periodic alternating structure can further optimize the stress distribution inside the coating, so that the prepared kitchen knife can maintain good sharpness and wear resistance during long-term cutting use.
[0099] Example 1
[0100] This embodiment provides a kitchen knife with a high-hardness, wear-resistant composite coating.
[0101] In this embodiment, the kitchen knife base is made of 9Cr18MoV stainless steel and undergoes stamping, heat treatment, surface grinding, and fine grinding of the blade edge to meet the requirements for food cutting.
[0102] A high-hardness, wear-resistant composite coating is formed on the blade surface of the kitchen knife substrate. The high-hardness, wear-resistant composite coating includes a bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer.
[0103] The bonding layer is located between the kitchen knife substrate and the high-entropy alloy layer to improve the interfacial bonding performance between the composite coating and the kitchen knife substrate. The high-entropy alloy layer and the high-entropy nitride layer form a multi-layer composite structure with periodic alternation. The high-entropy alloy layer provides good toughness and impact resistance, while the high-entropy nitride layer provides high hardness and wear resistance.
[0104] In this embodiment, the bonding layer is formed by depositing a titanium target using an arc ion plating process, and the bonding layer thickness is 400 nm.
[0105] A multilayer composite structure is formed by depositing high-entropy alloy layers and high-entropy nitride layers in a periodic alternation manner. The thickness ratio of the single layer of high-entropy nitride layer to high-entropy alloy layer is 4:1. The multilayer composite structure includes 16 modulation cycles, and the thickness of each modulation cycle is about 250nm.
[0106] The specific preparation process is as follows:
[0107] After the knife body has been sharpened, it is placed in an ultrasonic cleaning line and ultrasonically cleaned with acetone and anhydrous ethanol in sequence to remove oil, grinding residue and attached impurities from the surface of the knife body. Then, it is dried with hot air and the dried knife body is mounted on the workpiece rack of the vacuum coating equipment.
[0108] The vacuum coating chamber is evacuated to achieve a back vacuum level of 2.0 × 10⁻⁶. -3 The temperature is below Pa, and the heating device is turned on to raise the temperature of the coating chamber to 450°C.
[0109] Argon gas was then introduced into the vacuum coating chamber, and the working pressure was controlled at 0.5 Pa. At the same time, the bias voltage of the kitchen knife substrate was adjusted to -250 V. Argon ions were generated by arc-enhanced glow discharge to bombard and etch the surface of the kitchen knife substrate for 45 minutes to remove the oxide layer and residual contaminants on the substrate surface and improve the bonding strength of subsequent coatings.
[0110] After ion etching and cleaning, a bonding layer was deposited using an arc ion plating process under an argon protective atmosphere, with a titanium target as the target source. During the deposition process, the argon pressure was controlled at 0.5 Pa, the titanium target current at 100 A, the bias voltage of the kitchen knife substrate at -100 V, and the deposition time at 10 min, resulting in a titanium bonding layer with a thickness of approximately 400 nm.
[0111] Subsequently, an AlTiCrMoSiNb high-entropy alloy target was used as the arc target, and a high-entropy alloy layer was deposited under an argon atmosphere without nitrogen introduction. The argon pressure was controlled at 0.4 Pa, the target current at 140 A, and the bias voltage of the kitchen knife substrate at -80 V. The initial atomic percentage ratio of each metal element in the AlTiCrMoSiNb high-entropy alloy target was: Al 16%, Ti 20%, Cr 20%, Mo 10%, Si 8%, and Nb 26%.
[0112] After the high-entropy alloy layer is deposited, nitrogen gas is introduced into the vacuum coating chamber to convert the working atmosphere into a nitrogen reaction atmosphere, where a high-entropy nitride layer is deposited. The nitrogen pressure is controlled at 2.0 Pa, the target current at 140 A, and the knife substrate bias voltage at -80 V.
[0113] After completing one high-entropy alloy layer / high-entropy nitride layer modulation cycle, the nitrogen input is turned off, restoring the argon protective atmosphere in the coating chamber, and the high-entropy alloy layer is deposited again; then nitrogen is introduced again to form the high-entropy nitride layer. Through the periodic alternation of the above-mentioned argon atmosphere and nitrogen reaction atmosphere, and by adjusting the deposition time according to the deposition rate under different atmosphere conditions, the high-entropy alloy layer and the high-entropy nitride layer are deposited alternately at a single-layer thickness ratio of 1:4, ultimately obtaining a high-hardness wear-resistant composite coating consisting of 16 modulation cycles.
[0114] Example 2
[0115] This embodiment provides a kitchen knife with a high-hardness, wear-resistant composite coating.
[0116] This embodiment uses the same kitchen knife substrate pretreatment process and bonding layer preparation process as in Embodiment 1.
[0117] When depositing the high-entropy alloy layer, the argon pressure was controlled at 0.35 Pa, the target current at 130 A, and the substrate bias at -70 V.
[0118] When depositing the high-entropy nitride layer, the nitrogen pressure was controlled at 1.8 Pa, the target current at 130 A, and the substrate bias at -90 V.
[0119] By alternating between argon deposition environment and nitrogen reaction deposition environment, a multilayer composite structure of high-entropy alloy layer / high-entropy nitride layer containing 12 modulation cycles was obtained.
[0120] In this embodiment, the high-entropy nitride layer and the high-entropy alloy layer form a periodically alternating multilayer composite structure. The thickness ratio of the single layer of the high-entropy nitride layer to the single layer of the high-entropy alloy layer is 3:1. The multilayer composite structure includes 12 modulation cycles, and the thickness of each modulation cycle is 220nm.
[0121] Example 3
[0122] This embodiment provides a kitchen knife with a high-hardness, wear-resistant composite coating.
[0123] In this embodiment, the high-entropy nitride layer and the high-entropy alloy layer form a multilayer composite structure with periodic alternation. The thickness ratio of the single layer of the high-entropy nitride layer to the single layer of the high-entropy alloy layer is 4:1. The multilayer composite structure includes 20 modulation cycles, and the thickness of each modulation cycle is 290nm.
[0124] In the preparation process of this embodiment:
[0125] During ion bombardment cleaning, the argon pressure was controlled at 0.6 Pa, the substrate bias voltage was -200 V, and the etching time was 50 min.
[0126] During the deposition of the high-entropy alloy layer, the argon pressure was controlled at 0.5 Pa, the target current was 150 A, and the substrate bias voltage was -100 V.
[0127] During the deposition of the high-entropy nitride layer, the nitrogen pressure was controlled at 2.5 Pa, the target current was 150 A, and the substrate bias voltage was -100 V.
[0128] The final result is a high-entropy alloy / high-entropy nitride periodically alternating multilayer composite coating with 20 modulation cycles.
[0129] The main difference between this embodiment and Embodiment 1 lies in the composition ratio of the high-entropy alloy layer and the high-entropy nitride layer, as well as the number of modulation cycles.
[0130] Example 4
[0131] This embodiment provides a kitchen knife with a high-hardness, wear-resistant composite coating.
[0132] This embodiment adopts the high-hardness wear-resistant composite coating structure described in the aforementioned embodiment (II), that is, the high-entropy alloy layer and the high-entropy nitride layer form a continuous gradient structure.
[0133] In this embodiment, the preparation process of the kitchen knife substrate and the titanium bonding layer disposed on the surface of the kitchen knife substrate is the same as that in Example 1, and will not be repeated here.
[0134] A high-entropy alloy layer is formed on the surface of the titanium bonding layer, and the high-entropy alloy layer is gradually transitioned to a high-entropy nitride layer containing Er and B elements by adjusting the reaction atmosphere, thereby forming a composite coating with continuous composition gradient and phase structure gradient.
[0135] In this embodiment, during the deposition process, the composition of the reactive gas and the target material is adjusted to allow the coating to gradually transition from a high-entropy alloy layer to a high-entropy nitride layer. The specific preparation process is as follows:
[0136] After the titanium bonding layer is formed, an AlTiCrMoSiNb high-entropy alloy target is first used as the main arc target for deposition. The high-entropy alloy layer is formed in an atmosphere with an argon pressure of 0.5 Pa for 10 min.
[0137] Subsequently, while maintaining the high-entropy alloy main target current at 140A and the substrate bias voltage at -80V, an Er-B alloy target with a purity greater than 99.9% (where the atomic ratio of Er to B is 1:2) was activated as an auxiliary arc source, and the Er-B alloy target current was controlled at 35A. Simultaneously, nitrogen gas was introduced, and the nitrogen pressure in the vacuum chamber was continuously and uniformly increased from 0.5Pa to 2.5Pa at a rate of 0.05Pa / min. The entire gradient deposition process lasted 40 minutes. During this process, due to the synchronous effect of nitrogen gas pressure and the auxiliary Er-B alloy target, Er and B elements were gradually introduced into the coating. The coating composition gradually transitioned from a high-entropy alloy layer to a high-entropy nitride layer rich in Er and B, ultimately obtaining a gradient composite coating with a thickness of approximately 4.2μm and continuously changing composition and phase structure.
[0138] Performance Testing and Results Analysis
[0139] (1) Coating cross-sectional morphology and thickness test
[0140] The cross-sectional morphology of the high-hardness wear-resistant composite coatings prepared in Examples 1-4 was observed using field emission scanning electron microscopy, and the structural characteristics of the coatings were analyzed by cross-sectional energy dispersive spectroscopy. During the testing process, kitchen knives prepared in Examples 1-4 were used to prepare cross-sections perpendicular to the blade direction. After mechanical grinding and ion polishing, the coating cross-sections were observed.
[0141] Test results show that:
[0142] The composite coatings prepared in Examples 1-3 all exhibited a distinct multilayered modulated structure. Among them, a periodic layered structure composed of alternating high-entropy alloy layers and high-entropy nitride layers could be observed above the titanium bonding layer. The interfaces between the modulated layers were clear, and no obvious pores, cracks, or continuous through-thickness defects were observed.
[0143] In Example 1, the composite coating includes 16 high-entropy alloy layer / high-entropy nitride layer modulation cycles, with a single modulation cycle thickness of approximately 250 nm and a total coating thickness of approximately 4.5 μm.
[0144] In Example 2, the composite coating includes 12 modulation cycles, with a thickness of approximately 220 nm for each modulation cycle and a total coating thickness of approximately 2.7 μm.
[0145] In Example 3, the composite coating includes 20 modulation cycles, with a thickness of approximately 290 nm for each modulation cycle and a total coating thickness of approximately 5.8 μm.
[0146] In Example 4, due to the use of gradient deposition process, no obvious interfacial layering structure was observed. Instead, it showed a continuous gradient change characteristic from high-entropy alloy region to high-entropy nitride region. The elemental distribution inside the coating changed continuously, and no obvious abrupt change in composition interface appeared.
[0147] The above results show that the arc ion plating process used in this application can achieve stable deposition of high-entropy alloy layers and high-entropy nitride layers, and can controllably prepare periodic alternating structures or gradient structures by adjusting the reaction atmosphere.
[0148] (2) Elemental composition analysis of the modulation layer
[0149] Because the high-hardness wear-resistant composite coatings in Examples 1-3 employ a periodic alternation structure of high-entropy alloy layers / high-entropy nitride layers, the thickness of a single modulation layer is at the nanoscale. However, conventional EDS testing with its limited spatial resolution makes it difficult to accurately quantify the individual modulation layers. Therefore, to obtain the true elemental composition of each modulation layer, a single-layer film calibration method was used for component analysis.
[0150] Specifically, such as Figure 1 As shown, under the same deposition conditions as the kitchen knife substrate, rectangular block substrates (the same as the kitchen knife substrate) were used as test samples, and high-entropy alloy monolayer films and high-entropy nitride monolayer films with a thickness greater than 2 μm were deposited separately according to the arc ion plating process parameters corresponding to Examples 1 to 4.
[0151] Subsequently, elemental quantitative analysis was performed using an energy dispersive spectroscopy (EDS) instrument, and the elemental distribution inside the film was corrected by combining the results of X-ray photoelectron spectroscopy (XPS) depth profiling.
[0152]
[0153] (3) Phase structure analysis
[0154] The test samples prepared using the aforementioned (2) modulation layer elemental composition analysis were subjected to phase analysis of the coatings obtained in Examples 1-4 using an X-ray diffractometer (XRD). During the test, grazing incidence X-ray diffraction mode was used for detection, and Jade software combined with a standard PDF database was used to identify the phases of the diffraction peaks.
[0155] The results showed that the high-entropy alloy monolayer films in Examples 1-3 mainly exhibited a coexistence structure of face-centered cubic (FCC) and body-centered cubic (BCC) lattices. Among them, the FCC structure is beneficial to improving the plastic deformation capacity of the coating, giving the coating better crack resistance when the tool is subjected to impact load; while the BCC structure can improve the coating strength and shear resistance.
[0156] The high-entropy nitride monolayer films in Examples 1-3 all exhibit a single-phase face-centered cubic solid solution structure. Due to the presence of multiple elements such as Al, Ti, Cr, Mo, Si, and Nb in the nitride lattice, a lattice distortion effect is formed, which improves the coating's hardness and resistance to plastic deformation.
[0157] In the gradient composite coating obtained in Example 4, as the nitrogen content increases, the crystal structure gradually changes from a metallic solid solution structure to a face-centered cubic nitride structure, indicating the formation of a continuous phase structure gradient.
[0158] (4) Hardness and elastic modulus
[0159] The mechanical properties of the coatings were tested using a nanoindentation tester (Anton Paar TTX-NHT3) according to ISO 14577 standard specifications. The mechanical properties of the kitchen knife coatings obtained in Examples 1-4 were analyzed using the nanoindentation test method.
[0160] Before testing, the blade of a kitchen knife coated with a high-hardness wear-resistant composite coating was cut along a direction perpendicular to the blade, and the coating surface was finely polished by mechanical polishing to reduce the influence of micro-particle defects and surface roughness generated during the arc ion plating process on the indentation test results.
[0161] During the test, a Berkovich diamond indenter was used for loading. The indenter has a triangular pyramid structure with a vertex angle of 142.3°. Before the test, the Poisson's ratio of the coating material system was set to 0.30, and the load-displacement response curves during the indentation process were recorded using the instrument's loading program.
[0162] Ten test points were randomly selected for each sample for nanoindentation testing, with a spacing of more than 20 μm between test points to avoid stress interference between adjacent indentations. Each sample was tested three times, and the average of all test data was taken as the final test result.
[0163] The test results are shown in the table below:
[0164] Sample Coating structure Nanohardness HIT (GPa) Elastic modulus EIT (GPa) Example 1 16-period AlTiCrMoSiNb / AlTiCrMoSiNbN multilayer structure 36.8 382 Example 2 12-period AlTiCrMoSiNb / AlTiCrMoSiNbN multilayer structure 35.2 374 Example 3 20-cycle AlTiCrMoSiNb / AlTiCrMoSiNbN multilayer structure 38.5 395 Example 4 Er, B doping gradient high-entropy nitride structure 41.2 412
[0165] The test results show that the high-hardness wear-resistant composite coatings obtained in Examples 1 to 4 all have high nano-hardness and elastic modulus. Among them, the gradient composite coating obtained in Example 4 shows the highest hardness value and high elastic response capability.
[0166] For Examples 1-3, the high-entropy alloy layer and the high-entropy nitride layer form a periodically alternating modulation structure. The strong covalent bond structure and multi-element solid solution strengthening effect in the high-entropy nitride layer improve the coating hardness, while the high-entropy alloy layer can absorb external loads through plastic deformation, reducing the probability of crack initiation. This gives the coating both high hardness and impact resistance. In Example 3, the increased number of modulation cycles and interlayer interfaces further hinder dislocation movement and crack propagation, thus exhibiting higher nanoscale hardness.
[0167] In Example 4, the introduction of Er and B elements has two effects: on the one hand, it generates lattice distortion strengthening effect, which improves the coating's resistance to plastic deformation; on the other hand, the continuous gradient structure reduces the interfacial stress concentration during the transformation of the high-entropy alloy layer to the high-entropy nitride layer, which makes the coating have higher hardness and elastic recovery ability.
[0168] (5) Combined strength test
[0169] The bonding performance between the composite coatings obtained in Examples 1-4 and the kitchen knife substrate was evaluated using a film-substrate adhesion scratch test method. The test equipment employed a continuous load scratch tester, which used a diamond conical indenter to scratch the coating surface. By recording the frictional force, acoustic emission signals, and changes in scratch morphology during the scratching process, the critical load corresponding to coating failure was determined.
[0170] The specific test conditions are as follows: a diamond conical indenter with a radius of 200 μm was used; the initial load was set to 5 N; the final load was set to 80 N; the loading rate was 10 N / min; and the scratch length was 5 mm. After the test, the morphology of the scratched area was observed using a scanning electron microscope, and the critical load at which the coating first peels off, cracks, or fails at the interface was determined by combining the acoustic emission abrupt change points.
[0171] Sample Critical bonding load Lc / N Example 1 42.6N Example 2 39.8N Example 3 44.1N Example 4 48.5N
[0172] The test results show that the composite coatings obtained in Examples 1-4 all exhibit high film-substrate bonding strength. In Examples 1-3, the addition of a titanium bonding layer improves the interfacial transition between the coating and the 9Cr18MoV substrate. Simultaneously, the high-entropy alloy layer provides good plasticity buffering, reducing interfacial stress between the hard nitride layer and the substrate. In Example 4, the continuous gradient transition from the high-entropy alloy layer to the Er and B-containing high-entropy nitride layer avoids the abrupt interface found in traditional multilayer structures, thus resulting in even higher bonding strength.
[0173] (6) Tribological and wear performance test
[0174] The tribological properties of the high-hardness wear-resistant composite coatings obtained in Examples 1-4 were tested using a ball-disc tribological testing machine. During the test, alumina ceramic balls were used as the grinding material to simulate the tribological environment of the blade of a kitchen knife during long-term use.
[0175] The specific test conditions are as follows: grinding ball material: Al2O3 ceramic ball; grinding ball diameter: 6mm; load: 5N; sliding speed: 100mm / s; sliding distance: 1000m; test environment: room temperature air environment.
[0176] The friction coefficient variation curve was recorded in real time during the test. After the test, a three-dimensional white light interferometer was used to measure the cross-sectional area of the wear track and calculate the wear rate. Where: W is the wear rate; V is the wear volume; F is the normal load; and L is the sliding distance.
[0177] Sample <![CDATA[Wear rate / (×10 -7 mm³ / Nm)]]> Example 1 1.75 Example 2 1.91 Example 3 1.66 Example 4 1.35
[0178] The test results show that in Examples 1-3, the high-entropy nitride layer, as the main wear-resistant layer, has high hardness due to its single-phase face-centered cubic solid solution structure. Simultaneously, the high-entropy alloy layer can absorb localized stress generated during friction, thereby reducing the tendency for crack propagation. In Example 4, the use of Er and B elements to dope and form a continuous gradient structure results in a more stable lattice structure within the coating, while avoiding stress concentration at periodic interfaces, thus exhibiting the lowest coefficient of friction and the lowest wear rate.
[0179] In summary, the high-hardness wear-resistant composite coating provided in this application embodiment can significantly improve the surface hardness, film-base bonding performance, and long-term wear resistance of kitchen knife blades, effectively improving the problems of rapid blade wear and insufficient durability in traditional kitchen knives during long-term use.
[0180] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. For those skilled in the art, it will be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-hardness, wear-resistant composite coating, characterized in that, The high-hardness wear-resistant composite coating is applied to the cutting edge surface of a cutting tool by arc ion plating. The high-hardness wear-resistant composite coating includes a high-entropy alloy layer and a high-entropy nitride layer, wherein the high-entropy alloy layer and the high-entropy nitride layer form a gradient transition structure or a periodically alternating multilayer composite structure. The high-entropy alloy layer comprises aluminum, titanium, chromium, molybdenum, silicon, and niobium, and its phase structure is a hybrid structure of face-centered cubic and body-centered cubic lattices.
2. The high-hardness wear-resistant composite coating according to claim 1, characterized in that, The high-entropy alloy layer contains the following elements by atomic percentage: 12%–18% aluminum, 18%–25% titanium, 18%–25% chromium, 8%–12% molybdenum, 5%–10% silicon, and 18%–25% niobium.
3. The high-hardness wear-resistant composite coating according to claim 1, characterized in that, The elements of the high-entropy nitride layer include nitrogen, aluminum, titanium, chromium, molybdenum, silicon, and niobium, and the phase structure of the high-entropy nitride layer is a single-phase face-centered cubic solid solution structure.
4. The high-hardness wear-resistant composite coating according to claim 3, characterized in that, The high-entropy alloy layer and the high-entropy nitride layer form a periodically alternating multilayer composite structure; The high-entropy nitride layer comprises the following elements by atomic percentage: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, and niobium 7%–12%.
5. The high-hardness wear-resistant composite coating according to claim 4, characterized in that, The thickness ratio of the high-entropy nitride layer to the high-entropy alloy layer is 3 to 4:1; The multilayer composite structure formed by the high-entropy nitride layer and the high-entropy alloy layer includes 12 to 20 modulation cycles, and the thickness of each modulation cycle is 200 nm to 300 nm.
6. The high-hardness wear-resistant composite coating according to claim 1, characterized in that, The high-entropy alloy layer and the high-entropy nitride layer form a gradient transition structure. The high-entropy nitride layer contains the following elements by atomic percentage: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, niobium 7%–12%, erbium 0.1%–2.0%, and boron 0.5%–5.0%.
7. The high-hardness wear-resistant composite coating according to claim 1, characterized in that, The high-hardness wear-resistant composite coating also includes a bonding layer disposed between the blade surface and the high-entropy alloy layer. The bonding layer is formed by an arc ion plating process on a titanium target, and the thickness of the bonding layer is 300 nm to 500 nm.
8. A cutting tool, characterized in that, The knife is a kitchen knife, and the blade surface of the knife is provided with a high-hardness wear-resistant composite coating as described in any one of claims 1 to 7.
9. A cutting tool according to claim 8, characterized in that, The high-hardness wear-resistant composite coating comprises a bonding layer, a high-entropy alloy layer, and a high-entropy nitride layer; the bonding layer is formed by an arc ion plating process using a titanium target. The high-entropy alloy layer comprises the following elements by atomic percentage: 12%–18% aluminum, 18%–25% titanium, 18%–25% chromium, 8%–12% molybdenum, 5%–10% silicon, and 18%–25% niobium; The high-entropy nitride layer comprises the following elements by atomic percentage: nitrogen 40%–50%, aluminum 6%–10%, titanium 9%–14%, chromium 9%–14%, molybdenum 3%–7%, silicon 2%–6%, and niobium 7%–12%; The thickness ratio of the high-entropy nitride layer to the high-entropy alloy layer is 4:1; the high-entropy alloy layer and the high-entropy nitride layer form a periodically alternating multilayer composite structure, which includes 16 modulation cycles, and the thickness of each modulation cycle is 200nm to 300nm.
10. A method for preparing a cutting tool according to claim 9, characterized in that, The preparation method includes: The sharpened kitchen knife body is cleaned and dried in an ultrasonic cleaning line, and then mounted on the workpiece rack in the vacuum coating chamber; the vacuum coating chamber is evacuated to a back vacuum level of 1.5 × 10⁻⁶. -3 Pa ~ 3.0 × 10 -3 Pa, and the temperature is increased to 400℃~480℃; Argon gas is introduced into the vacuum coating chamber, and the gas pressure is controlled at 0.3 Pa to 0.6 Pa. The bias voltage of the kitchen knife substrate is controlled at -200 V to -300 V. The surface of the kitchen knife substrate is subjected to argon ion bombardment etching and cleaning for 25 min to 50 min. Using a titanium target as the target source, the bonding layer is deposited on the surface of the kitchen knife substrate using an arc ion plating process. Using an AlTiCrMoSiNb high-entropy alloy target as the arc target; under an argon atmosphere without nitrogen, turn on the arc target power supply, control the target current to be 120A~160A, and the substrate bias voltage to be -60V~-120V, and deposit the high-entropy alloy layer on the bonding layer. Under a nitrogen atmosphere, the gas pressure is controlled at 1.5 Pa to 3 Pa, the arc target power supply is turned on, the target current is controlled at 120 A to 160 A, and the substrate bias voltage is -60 V to -120 V, and the high-entropy nitride layer is deposited. By alternating the introduced gas atmosphere and controlling the deposition time, the high-entropy alloy layer and the high-entropy nitride layer are periodically deposited alternately at a single-layer thickness ratio of 1:4, forming a multilayer composite structure containing 16 modulation cycles with a thickness of 200nm to 300nm for each modulation cycle.